Seasonal Variations of Radiocarbon Content in Plant Leaves in a 14C-Depleted Area. Issue 3 (2015) - Baydoun, Rana; El Samad, Omar; Nsouli, Bilal; Younes, Ghassan
Abstract : The determination of radiocarbon content in biogenic samples such as tree leaves and short-lived plants is crucial when studying the anthropogenic impact on the ecosystem and for detecting any alteration in stable and radioactive CO2 . A total of 76 samples of evergreen and deciduous tree leaves as well seasonal plants were collected in winter, spring, and summer. Sampling was carried out from rural villages located in Mount Lebanon Province, Lebanon. Based on the data obtained from a previous study carried out in autumn, which showed that the selected sites are characterized by depletion of 14 C caused by the releases of pollutants and CO2 from a cement factory in the region, further investigation was carried out in the present work to determine possible significant seasonal variations in Δ 14 C values. Reference samples of identical species were collected in the same period from a clean zone. The conventional 14 C method was used to determine the carbon isotopic ratio. Δ 14 C data are compared to those obtained in autumn. 14 C concentration in the studied sites was significantly lower than in the clean area in all seasons. ANOVA tests showed that there is a significant seasonal variation for deciduous leaves and seasonal plants, while this difference was not significant in evergreen leaves. In addition, no significant variation was recognized for different species in the same season.